Within the COVID-19 pandemic are rates of depression within minoritized populations different compared to white individuals in the United States? - Pasha Farahi; Andrea Eugenia Arce Nunez; Amy Adkins; Aya Youssef; Jasmyne Khan (OSF Registries, 2022)
The pandemic has caused many to be under tremendous amounts of stress, especially racial minorities due to having more financial, family, and health issues. With so much worry around the country the state of people’s mental health could be thought to decline as a result. The state of an individual's mental health is also in direct correlation to their chances of becoming depressed.
Keywords: Social and Behavioral Sciences